Cost allocation for cross-border transmission lines in the BBIN sub-region using Game theory - Khem Gyanwali,; Ayshuma Gautam, (Journal of Innovations in Engineering Education, 2024)
The BBIN sub-region - Bangladesh, Bhutan, India, and Nepal - are witnessing a significant surge in electricity demand, accompanied by an uneven distribution of resources and consumption patterns across the region. Optimizing the unevenly distributed energy resources through a harmonized generation mix, tailored to the distinct load patterns and demands of individual nations, creates opportunities for enhanced electricity trade through multilateral cooperation. To facilitate this, the region has been conceptualized into four nodes connected by five interconnections: Bangladesh-Bhutan, Bangladesh-India, Bangladesh-Nepal, Bhutan-India, and India. While electricity trade has existed historically, a systematic approach to allocating the costs of cross-border transmission infrastructure has not been adopted. This study quantifies the benefits of regional electricity trade and proposes cost-sharing mechanisms using methodologies rooted in Game Theory, particularly the Shapley Value, alongside cooperative game theory, to ensure equitable cost distribution. A dynamic optimal power generation mix model reveals that the grand coalition - where all nations cooperate - is the most efficient configuration. In this scenario, India incurs the highest transmission line cost, reflective of its substantial size and electricity demand.